2013
DOI: 10.1111/manc.12000
|View full text |Cite
|
Sign up to set email alerts
|

MetaTaylor Rules for theUKandAustralia; Accommodating Regime Uncertainty in Monetary Policy Analysis Using Model Averaging Methods

Abstract: This paper provides a characterization of UK and Australian monetary policy within a Taylor rule framework, accommodating uncertainties about the nature and duration of policy regimes in a flexible but easy‐to‐implement analysis. Our approach involves estimation and inference based on a set of Taylor rules obtained through linear regression methods, but combined into a ‘meta’ rule using model averaging techniques. Using data that were available in real time, the estimated version of the meta Taylor rule provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Lee et al (2011) calls the resulting rule the "meta Taylor rule" and employs it to investigate U.S. monetary policy. Lee et al (2012) does the same with the U.K. and Australian monetary policies. The results demonstrate that the novel approach is useful and applicable in terms of both behavioral modelling and inference perspective, offering an overall highly flexible instrument with which to model and describe policymakers" decisions.…”
Section: Related Literaturementioning
confidence: 94%
“…Lee et al (2011) calls the resulting rule the "meta Taylor rule" and employs it to investigate U.S. monetary policy. Lee et al (2012) does the same with the U.K. and Australian monetary policies. The results demonstrate that the novel approach is useful and applicable in terms of both behavioral modelling and inference perspective, offering an overall highly flexible instrument with which to model and describe policymakers" decisions.…”
Section: Related Literaturementioning
confidence: 94%
“…Cukierman and Muscatelli (2008) and Kulikauskas (2014) found similar evidence for the European Central Bank. Maza and Sanchez-Robles (2013) found that the Taylor rule perfectly fit the monetary policy actions of the European Central Bank between 1999to 2002and 2007to 2009. Lee et al (2013 found that there were sizeable shifts in the Bank of England's monetary policy following the financial crisis.…”
Section: The Taylor Rulementioning
confidence: 99%
“…Molodtsova, Nikolsko-Rzhevskyy, and Papell (2011) showed that predictability is found with both one quarter ahead and longer horizon forecasts. Lee, Olekalns, and Shields (2013) indicated that with the use of data that are available in real time, the Taylor rule useful in the United Kingdom and Australia. Both of the dispersions of output and inflation are examined in this study.…”
Section: Estimated Equationsmentioning
confidence: 99%